HUBUNGAN ANTARA MENTAL TOUGHNESS DAN RISK PERCEPTION PADA PENDAKI GUNUNG PEMULA - Nst, Filzah Meutia; Ningsih, Yuninda Tria (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
This research aims to determine the relationship between mental toughness and risk perception in beginner climbers. The research method is by using quantitative correlational methods. The subjects of this research were 200 beginner mountain climbers in West Sumatra with the help of Google forms, social media and research questionnaires. The data measuring tool uses a risk perception scale and a mental toughness scale. The data collection technique used in this research uses a purposive sumpling technique by establishing several criteria. The data analysis technique used is product moment correlation with the help of IBM SPSS Statistics 20. The results of the hypothesis test are r = -0.684 and p = 0.00 < 0.05 with Ha accepted, there is a significant negative relationship between mental toughness and risk perception in beginner mountain climber. This means that the higher the mental toughness of novice mountain climbers, the lower the risk perception of novice mountain climbers. Conversely, the lower the mental toughness of novice climbers, the higher the risk perception of novice climbers.